2011
DOI: 10.1088/0964-1726/20/9/094010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of pressure-adaptive honeycomb and its application to wing morphing

Abstract: Current, highly active classes of adaptive materials have been considered for use in many different aerospace applications. From adaptive flight control surfaces to wing surfaces, shape-memory alloy (SMA), piezoelectric and electrorheological fluids are making their way into wings, stabilizers and rotor blades. Despite the benefits which can be seen in many classes of aircraft, some profound challenges are ever present, including low power and energy density, high power consumption, high development and instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…Murray et al [37,38] filled honeycombs with a lossy polymer in order to achieve a high stiffness structure with higher damping. What is more, Vos et al [39] filled hexagonal cells with pneumatic bladders for trailing edge morphing.…”
Section: Introductionmentioning
confidence: 99%
“…Murray et al [37,38] filled honeycombs with a lossy polymer in order to achieve a high stiffness structure with higher damping. What is more, Vos et al [39] filled hexagonal cells with pneumatic bladders for trailing edge morphing.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible mechanical systems, such as morphing wings, have been proposed to adapt wing geometry to changing flight conditions [4], seeking to increase performance at a range of air-speeds [5], reduce vibrations [6], increase maximum lift [7], decrease drag [8], and augment control of the vehicle [9]. However, scalable manufacturing and integration with traditional flight systems remain an open challenge [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some proposed adaptive aerostructures leverage planar configurations that have much higher stiffness across an orthogonal out-of-plane axis that is oriented to maintain stiffness in one or more dimensions while allowing orthogonal dimensions to retain low stiffness for passive elastic behavior or ease of actuation. Example technologies include specialized honeycombs [8], corrugated designs [12], and custom compliant mechanism designs such as those developed by Kota et al [13]. Planar designs generally choose a single loading plane to achieve airfoil camber morphing, span-wise bending, or span extension.…”
Section: Introductionmentioning
confidence: 99%
“…By using natural examples, the world's highest mass-specific actuator energy density actuator class was being developed as shown in Figure 4. [47][48][49][50] By using Pressure Adaptive Honeycomb (PAH), it was shown that the amount of work achieved per kg added to the aircraft for flight control can be maximized if pressure adaptive honeycomb actuators are used. Because these actuators use only FAR-25 certifiable materials operating strictly in the "infinite life" stress-strain zone on S-n curves, they are inherently built to be compatible with certifiable aircraft.…”
Section: Introductionmentioning
confidence: 99%